2017
DOI: 10.1186/s12864-017-3640-7
|View full text |Cite
|
Sign up to set email alerts
|

The Krüppel-like factor 9 cistrome in mouse hippocampal neurons reveals predominant transcriptional repression via proximal promoter binding

Abstract: BackgroundKrüppel-like factor 9 (Klf9) is a zinc finger transcription factor that functions in neural cell differentiation, but little is known about its genomic targets or mechanism of action in neurons.ResultsWe used the mouse hippocampus-derived neuronal cell line HT22 to identify genes regulated by Klf9, and we validated our findings in mouse hippocampus. We engineered HT22 cells to express a Klf9 transgene under control of the tetracycline repressor, and used RNA sequencing to identify genes modulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 81 publications
4
71
0
Order By: Relevance
“…By contrast, we found statistically significant increases in the KLF13 ChIP signal after dox treatment at the promoters of each of the four genes tested: Prkaca (3 fold), Rap1a (3.4 fold), Calm3 (3.3 fold) and Adcy6 (2.6 fold). Of the other three genes analyzed by targeted RTqPCR (Rapgef3, Tiam1 and Vav2), our ChSP-seq analyses (Knoedler et al, 2017;Ávila-Mendoza et al, 2020) showed that Rapgef3 has a KLF9 but not a KLF13 peak at its promoter (although there are strong KLF13 peaks at adjacent genes; see Supplementary Figure 1B), Vav2 has peaks for both KLFs, but Tiam1 has no peaks for either KLF. Using the genomic region covered by the KLF9 peak at the promoter of the Rapgef3 gene as the target sequence for Figure 1C).…”
Section: Klf9 and Klf13 Associate In Chromatin At Promoters Of Camp Smentioning
confidence: 84%
See 1 more Smart Citation
“…By contrast, we found statistically significant increases in the KLF13 ChIP signal after dox treatment at the promoters of each of the four genes tested: Prkaca (3 fold), Rap1a (3.4 fold), Calm3 (3.3 fold) and Adcy6 (2.6 fold). Of the other three genes analyzed by targeted RTqPCR (Rapgef3, Tiam1 and Vav2), our ChSP-seq analyses (Knoedler et al, 2017;Ávila-Mendoza et al, 2020) showed that Rapgef3 has a KLF9 but not a KLF13 peak at its promoter (although there are strong KLF13 peaks at adjacent genes; see Supplementary Figure 1B), Vav2 has peaks for both KLFs, but Tiam1 has no peaks for either KLF. Using the genomic region covered by the KLF9 peak at the promoter of the Rapgef3 gene as the target sequence for Figure 1C).…”
Section: Klf9 and Klf13 Associate In Chromatin At Promoters Of Camp Smentioning
confidence: 84%
“…Our previous genome-wide analyses using ChSP-seq in HT22 cells (Knoedler et al, 2017;Ávila-Mendoza et al, 2020) found that FIGURE 1 | KLF9 regulates cAMP signaling pathway genes in HT22 cells. We previously conducted an RNA sequencing experiment in the HT22-TR/TO-Klf9 cell line treated with or without doxycycline for 8 h to induce the Klf9 transgene (Knoedler et al, 2017). We analyzed differentially regulated genes in the context of the Kyoto Encyclopedia Genes and Genomes signaling pathways.…”
Section: Klf9 and Klf13 Associate In Chromatin At Promoters Of Camp Smentioning
confidence: 99%
“…KLF9 is a well‐known transcriptional regulator, although its function during development is not well studied. KLF9 collectively associates with either transcriptional co‐activators or co‐repressors to influence the expression levels of genes . Our previous studies demonstrated that STRAP negatively modulates Sp1‐dependent transcription , suggesting an important role of STRAP in regulating the binding of TFs to cis‐acting sequences.…”
Section: Discussionmentioning
confidence: 99%
“…4) show that Klf9 mediates the pro-inflammatory gene expression induced by chronic cortisol exposure that we reported previously 23 . Among other things Klf9 functions as a transcriptional repressor 10,11 , and in mouse macrophages as an incoherent feedforward regulator of the GR target klf2 12 , which functions to control inflammation 47 . Further work is needed to determine how klf9 contributes to proinflammatory gene expression in response to chronic cortisol exposure, which could either be directly as a feedforward activator (possibly via effects on metabolism), indirectly as a feedforward repressor of an antiinflammatory regulator like Klf2, or both.…”
Section: Discussionmentioning
confidence: 99%
“…A GR target gene that was recently shown to mediate circadian regulation of cell proliferation in human epidermis is KLF9 6 , which encodes a ubiquitously expressed 7 member of the krüppel-like family of zinc finger transcription factors. Klf9 is a repressor important for neurogenesis and control of neural plasticity [8][9][10][11] , and is a central player in the GR-responsive gene regulatory network in macrophages 12 , where it functions to repress another GR target gene, klf2. In this context the GR, klf9, and klf2 constitute a regulatory circuit known as an 'incoherent type-1 feed-forward loop' (i1-FFL) 12 , a network motif commonly used to generate pulsatile dynamics and accelerate responses [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%